Les affaires internationales du Chili des « Temps nouveaux » (Note) - Peña, Orlando (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1996)
Albeit the end of military dictatorship, a significant part of Chile's international affairs is still conditioned by some of the great principles established at the time. In spite of this, President Patricio Aylwin's administration was able to set up a relationship with other world countries different from that imposed under General Pinochet's regime. The nomination, in May 1994, of Eduardo Frei and a new Cabinet at the head of the country has led to another series of attempts to change the way international affairs are managed. The rate of success of such attempts depends upon the ability of the government coalition to go beyond the blind acceptance of international market forces, to set up appropriate negociations for Chile's membership in various world organisations, such as APEC, Mercosur and NAFTA, and above all, to break the barriers built by the upholding of important sectors of the former military regime.